Under water video footage from Weddell seal NEU2024_wed_a_f_03_1 taken by seal mounted deployments during expedition ANT-Land_2024_SEAEIS (NEU2024) - Henning Schröder; Christoph Held; Horst Bornemann (PANGAEA, 2025)
SEAls and cryobenthic communities at the Ekström Ice Shelf (SEAEIS) applies biologging technologies for studying the foraging ecology of Weddell seals with a direct link to the investigation of cryobenthic invertebrate communities beneath the Ekström Ice Shelf at Atka Bay. Incidences of cryobenthic communities beneath ice shelves are rare and recent discoveries. Combined seal- and ROV-borne imagery and novel sampling technologies led to the discovery of a cryobenthic isopod community (Antarcturus cf. spinacoronatus Schultz 1978), being attached head-down to the underside of floating shelf ice at Drescher Inlet (Riiser-Larsen Ice Shelf) at depths of around 80-150 m (Watanabe et al. 2006; Bornemann et al. 2016). These "hanging gardens" may represent a food horizon where seals could benefit from a local hotspot of high biologic activity. The presence of isopod aggregations explained a multimodal distribution of the seals extquotesingle dive depths known from earlier investigations at Drescher Inlet, and could probably also be indicative for increased abundances of seals in Areas of Ecological Significance (AES) at the interface between shelf and sea ice. However, the question whether the aforementioned findings are representative for the far-ranging high Antarctic ice shelves or even unique remains open, and factors contributing to AES and their stability over time are largely unexplored. Therefore, we proposed a synoptic field study at Atka Bay (Neumayer Station III), where earlier deployments of satellite-linked data loggers also showed a mode in the distribution of bottom times spent at water depths corresponding to the underside of the floating shelf ice, thus supporting the hypothesis of ice shelf associated foraging.